Post-translational signal peptide cleavage controls differential epitope recognition in the QP-rich domain of recombinant Theileria parva PIM - Casanova, C.L.; Xue, G.; Taracha, E.L.N.; Dobbelaere, D.A.E. (Elsevier, 2006)
The presence of the schizont stage of the obligate intracellular parasites Theileria parva or T. annulata in the cytoplasm of an infected leukocyte results in host cell transformation via a mechanism that has not yet been elucidated. Proteins, secreted by the schizont, or expressed on its surface, are of interest as they can interact with host cell molecules that regulate host cell proliferation and/or survival. The major schizont surface protein is the polymorphic immunodominant molecule, PIM, which contains a large glutamine- and proline-rich domain (QP-rd) that protrudes into the host cell cytoplasm. Analyzing QP-rd generated by in vitro transcription/translation, we found that the signal peptide was efficiently cleaved post-translationally upon addition of T cell lysate or canine pancreatic microsomes, whereas signal peptide cleavage of a control protein only occurred cotranslationally and in the presence of microsomal membranes. The QP-rd of PIM migrated anomalously in SDS-PAGE and removal of the 19 amino acids corresponding to the predicted signal peptide caused a decrease in apparent molecular mass of 24 kDa. The molecule was analyzed using monoclonal antibodies that recognize a set of previously defined PIM epitopes. Depending on the presence or the absence of the signal peptide, two conformational states could be demonstrated that are differentially recognized, with N-terminal epitopes becoming readily accessible upon signal peptide removal, and C-terminal epitopes becoming masked. Similar observations were made when the QP-rd of PIM was expressed in bacteria. Our observations could also be of relevance to other schizont proteins. A recent analysis of the proteomes of T. parva and T. annulata revealed the presence of a large family of potentially secreted proteins, characterized by the presence of large stretches of amino acids that are also particularly rich in QP-residues.